HOMOLOGI STRUKTURAL ANTARA SALIHARA DENGAN RUMAH ASAP DALAM SAMAN (Structural Homology of Salihara and the Smokehouse in Saman) - Muhammad Qadhafi (Kandai, 2022)
This study focuses on the problem of the relationship between the KUK/Salihara structure and the smokehouse structure in Ayu Utami's novel Saman. This study aims to find the relationship between the dominant position of KUK/Salihara and its structure and to describe the structural homology between KUK/Salihara and the Smokehouse in Saman. This study uses qualitative data collection methods. The researcher used Bourdieu's arena construction method and the Social Network Visualizer (SocNetV) application to visualize the structure. In addition, researchers also use SocNetV's “centrality analysis” feature to determine the centrality of an agent. The results of this study are: 1) KUK/Salihara occupies a dominant position in the modern Indonesian literary field because of the high level of cultural capital, social capital, and economic capital. The acquisition of these capitals is closely related to the role of KUK/Salihara as a mediator that connects the literary field with other cultural fields, making it easier for them to exchange capital and monopolize legitimacy; 2) structural homology between KUK/Salihara and Saman shows that: a) both carry the same doxa, namely "freedom”; b) the dominant position and central role of Wisanggeni in the structure of the Lubukrantau Smokehouse association actually represents the position and role of GM rather than the position and role of Ayu Utami in the KUK/Salihara structure; and c) other problems were found regarding the process of writing Saman's novel that needed further study.Penelitian ini menyoroti persoalan kaitan antara struktur KUK/Salihara dengan struktur perkumpulan di dalam novel Saman karya Ayu Utami. Penelitian ini bertujuan untuk menemukan kaitan antara posisi dominan KUK/Salihara dengan strukturnya dan untuk mendeskripsikan homologi struktural antara KUK/Salihara dengan perkumpulan rumah asap dalam Saman. Penelitian ini menggunakan metode pemerolehan data kualitatif. Peneliti menggunakan metode konstruksi arena Bourdieu dengan bantuan aplikasi Social Network Visualizer (SocNetV) untuk memvisualkan struktur. Selain itu, peneliti juga menggunakan fitur “centrality analysis” SocNetV untuk mengetahui sentralitas suatu agen. Hasil penelitian ini, yakni: 1) KUK/Salihara menempati posisi dominan di arena sastra Indonesia modern karena tingginya modal kultural, modal sosial, dan modal ekonomi. Pemerolehan modal-modal tersebut berkaitan erat dengan peran KUK/Salihara sebagai mediator yang menghubungkan arena sastra dengan arena kultural yang lain sehingga memudahkannya untuk melakukan pertukaran modal dan monopoli legitimasi; 2) homologi struktural antara KUK/Salihara dengan novel Saman karya Ayu Utami menunjukkan bahwa: a) keduanya mengusung doksa yang sama, yaitu “kebebasan”; b) posisi dominan dan peran sentral Wisanggeni dalam struktur perkumpulan rumah asap Lubukrantau justru merepresentasikan posisi dan peran GM daripada posisi dan peran Ayu Utami dalam struktur KUK/Salihara; dan c) ditemukannya persoalan lain mengenai proses penulisan novel Saman yang perlu dikaji lebih lanjut.